Accretion theory of ideation: evaluation regimes for ideation stages. (2019) - Sosa, Ricardo
Abstract : This paper presents an exercise on theory building to characterise design ideation. It starts by examining how early ideas are defined and evaluated in the literature. An essentialist view is identified that explains the creativity of a final design solution by the creative qualities of early ideas attributed by external judges. Criteria for a theory of ideation that does not rely on the primacy of essence are enumerated. Advanced professional practice is examined to understand evaluation of early ideas 'in the wild'. Accretion is then introduced as an analogical model to imaginatively drive definitions and conjectures about idea formation in the co-evolution of problem and design spaces. Vignettes from ideation episodes are used to illustrate an accretion theory of ideation. An accretion theory supports new ways to think about ideation as a complex formation process where creative solutions emerge from the synthesis of a multitude of fragmentary and partial ideas – or 'ideasimals'. An accretion theory of ideation helps to explain the creative value of a final design solution without relying on early ideas having a creative essence, because the creativity of a solution is viewed as emergent rather than present in early versions. An accretion lens is used to suggest new ideation metrics to study the qualities of idea fragments and the process of idea formation. Definitions and relevant assessment regimes for different stages of ideation are discussed. The paper concludes with a discussion on entailments of an accretion theory and next steps for this theory building enterprise.